The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1108/jhom-09-2019-0280
|View full text |Cite
|
Sign up to set email alerts
|

Changing to improve? Organizational change and change-oriented leadership in hospitals

Abstract: PurposeThis paper aims to fill gaps in one’s knowledge of the impact of organizational change on two outcomes relevant to hospital service quality (performance obstacles and physician job satisfaction) and in one’s knowledge of the role of middle manager change-oriented leadership in relation to the same outcomes. Further, the authors aim to identify how physician participation in decision-making is impacted by organizational change and change-oriented leadership, as well as how it mediates the relationships b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 65 publications
4
28
0
Order By: Relevance
“…The apparent simplicity of this process to reduce a waitlist belies the conflicts that require acknowledgement when implementing any organisational change, even one which has a relatively small and local impact (Matland, 1995). Improvement initiatives are often instigated from hospital executive managers, driven by health department policy, but change activity can be experienced by ground-level staff as additional work demands in an environment which is already at capacity (Øygarden et al , 2020). In the current study there was “bottom-up” implementation (Matland, 1995) where the instigator of the project was the senior neurologist who identified a mismatch between both policy objectives and aspirations of access and quality of care and the performance of his clinic.…”
Section: Discussionmentioning
confidence: 99%
“…The apparent simplicity of this process to reduce a waitlist belies the conflicts that require acknowledgement when implementing any organisational change, even one which has a relatively small and local impact (Matland, 1995). Improvement initiatives are often instigated from hospital executive managers, driven by health department policy, but change activity can be experienced by ground-level staff as additional work demands in an environment which is already at capacity (Øygarden et al , 2020). In the current study there was “bottom-up” implementation (Matland, 1995) where the instigator of the project was the senior neurologist who identified a mismatch between both policy objectives and aspirations of access and quality of care and the performance of his clinic.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that "it is more reasonable to interpret our finding as an indication that organizational changes which in the current health policy climate are often motivated by cutting costs and increasing control and efficiency may indeed create more work system performance obstacles" (11), adding that "participation in decisionmaking is an aspect of such engagement and should be encouraged and safeguarded by hospital leadership in change processes as well as in day-to-day operations" (11). There is literature that examines organizational change in hospitals in terms of change tactics and methods suggesting that those at lower levels should be given as much autonomy and flexibility as possible to implement change at their levels (12,13).…”
Section: Introductionmentioning
confidence: 94%
“…The main responsibility of Middle Managers is to keep the organization running, moving forward and making profit so that top management members can focus on bigger decisions about budgets, goals, and vision (Kahm and Ingelsson 2020 ; Øygarden et al 2020 ). Maintaining worker productivity is a major responsibility for Middle Managers, and the top management often sets productivity standards.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Middle Management is the backbone that all organizations have relied upon. The distinction in this level of management depends on the extent of its proximity to the theater of the lower levels in the organization, which make it obvious for all work processes, areas of improvement, shortcomings and development, (Kahm and Ingelsson 2020 ; Øygarden et al 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation